1990
DOI: 10.1037/0022-3514.58.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fortuitously activated constructs versus activated communication goals on person impressions.

Abstract: The relative impact of construct accessibility effects (i.e., the influence of accessible and applicable constructs) and communication goal effects (i.e., the influence of constructs activated through communication goals) on both the interpretation and transmission of ambiguous target information and Ss' private target impressions is examined. Whether communication goal effects can lead to recoding of target information is also examined. Ss were primed with either positive or negative trait constructs, were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 48 publications
7
92
0
Order By: Relevance
“…In particular the communicative context evoked by the recipient and the recipient's perceived characteristics have been shown to play an important role in this respect (e.g. Higgins, 1981;Kingsbury, 1968;Martijn, van der Pligt, & Spears, 1996;McCann & Higgins, 1992;Sedikides, 1990).…”
Section: Communication Categorization and Stereotypingmentioning
confidence: 99%
“…In particular the communicative context evoked by the recipient and the recipient's perceived characteristics have been shown to play an important role in this respect (e.g. Higgins, 1981;Kingsbury, 1968;Martijn, van der Pligt, & Spears, 1996;McCann & Higgins, 1992;Sedikides, 1990).…”
Section: Communication Categorization and Stereotypingmentioning
confidence: 99%
“…The important distinction between activation and application is evident in Sedikides's (1990) research, which showed that communication goals can override accessibility effects in impression formation. First, participants engaged in a task that primed either positive or negative trait attributes.…”
mentioning
confidence: 99%
“…These motivations are clearly at odds with the application of accessible racial stereotypes. Therefore, based on the research of Sedikides (1990) and Thompson et al (1994), one might expect that stereotypes of these groups that are activated through thought suppression may not be applied to subsequent impressions of group members. The motivation to avoid stereotyping these secondary targets (even in the absence of explicit suppression instructions) would mitigate against the influence of the activated stereotype.…”
mentioning
confidence: 99%
“…Characteristics were designed to be neither clearly negative nor positive. The ambiguous nature of these characteristics was validated in previous research (Sedikides, 1990).…”
Section: Methodsmentioning
confidence: 68%
“…Materials Information about the target group was patterned closely after that used to describe target individuals in previous SIB studies (Echterhoff et al, 2005b;Higgins & Rholes, 1978;McCann & Hancock, 1983;Sedikides, 1990), but modifi ed so that the characteristics described a group rather than an individual. Four characteristics used in recent studies (Echterhoff et al, 2005a(Echterhoff et al, , 2005b were adapted for use in the current study (see Appendix).…”
Section: Methodsmentioning
confidence: 99%